PENINGKATAN HASIL BELAJAR PENJASKES PADA POKOK BAHASAN MENGENAL BERBAGAI UPAYA DALAM MENJAGA KEBERSIHAN LINGKUNGAN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS IV SD NEGERI 53 BANDA ACEH TAHUN PELAJARAN 2012/2013 - Najaruddin Najaruddin (JURNAL TEMATIK, 2014)
Improved Learning Outcomes Of Physical Education On Subject About Various Efforts In Keeping Clean Environment Through Application Cooperative Learning Model Jigsaw Type In Class IV SD State 53 Banda Aceh Academic Year 2012/2013. The background of this research is the maximal activity of fourth grade students in the learning process in subjects physical education subject matter of keeping the environment that lead to learning outcomes most of them have not reached the KKM. This occurs because the educators still tend to use conventional learning models in each lesson with variations in other words the lack of use of the learning model in teaching and learning activities. This study aims to determine: 1) how the application of the Jigsaw cooperative learning model in studying the subject physical education subject matter keeping the environment in the fourth grade Elementary School 53 Banda Aceh, 2) if the jigsaw cooperative learning model to improve learning outcomes of students in penjasorkes fourth grade in the subject matter keeping the environment in the fourth grade Banda Aceh State 53 2012/2013 academic year. This research is Classroom Action Research (Classroom Action Research) aimed at improving student learning outcomes, especially in subjects dribble subject matter in order to achieve a minimum completeness criteria (KKM). The method used was action research in two cycles. The research was conducted in the fourth grade Banda Aceh State 53 Academic Year 2012/2013, amounting to 32 students. Data collection techniques using the test, interview and observation sheet. The results of the study at the time of the pretest obtained average value of student learning outcomes at the time of the pretest with classical completeness 0% with an average of 32.5. Increased by using cooperative learning model jigsaw, student learning outcomes can be improved which can be seen from the results of student learning classical completeness reached 65.63% with an average of 61.88 in the first cycle and increased to 100% with an average of 89 , 69 in the second cycle.